Strategi Adaptasi Pedagang Pasar Muntilan dalam Menghadapi Revitalisasi dan Maraknya Penggunaan E-commerce - Arivah, Azulfa; Hendrastomo, Grendi (Jurnal Pemberdayaan Masyarakat, 2024)
This research aims to: (1) to identify the adaptation of Muntilan Market traders in facing the impact of revitalization and the rampant use of e-commerce; (2) to identify the strategies carried out by traders in Muntilan Market to maintain and develop their business amid the rampant use of e-commerce and the impact of revitalization. This research is descriptive qualitative research with a case study research design. This research was conducted in Muntilan Market, Magelang, Central Java. Informants in this research are traders who sell secondary/tertiary needs. The data sources in this research are primary data and secondary data. Data collection was done by observation, interview, and documentation. The data analysis technique used is the Miles and Huberman model analysis technique. The results of this study indicate that: (1) Adaptations made by traders in Pasar Muntilan, especially traders who sell secondary/tertiary needs to deal with the impact of revitalization and the rampant use of e-commerce, including providing good service to buyers, selling products/merchandise at affordable prices, providing good quality goods to buyers, promoting merchandise through social media, opening stalls earlier, and establishing good relationships with fellow traders; (2) Strategies carried out by traders in Muntilan Market, especially traders who sell secondary/tertiary needs to maintain their business amid the widespread use of e-commerce and the impact of revitalization, namely by providing discounts / price cuts and giving gifts or gifts to buyers. While the strategy to develop their business, traders follow existing trends and add new collections of products / merchandise (product diversification).